2021
DOI: 10.1007/s10926-021-09991-6
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Minds: Group Cognitive-Behavioral Intervention for Sustainable Return to Work After a Sick Leave Due to Depression

Abstract: Background Depression is one of the major causes for sick leave and loss of productivity at work. Many studies have investigated return to work (RTW) interventions for people with common mental disorders. However, a paucity of studies has targeted depressive symptoms in the workplace, as well as work productivity. Objectives This study presents preliminary results on a novel group intervention based on cognitive behavioral principles in order to optimize sustainable RTW, by reducing clinical symptoms (anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
3
0
2
Order By: Relevance
“…Optimizing collaboration between the various RTW stakeholders is part of work-directed interventions, along with identifying barriers to return to work (Corbière et al, 2021; Jetha et al, 2021; MacEachen et al, 2020). For the job demands dimension, occupational therapists have also identified clinical interventions such as teaching strategies for managing relationships and emotions that can be associated with principles of cognitive-behavioral therapy (CBT), an approach on which are based most clinical interventions carried out in a RTW support context for people with CMDs (Corbière et al, 2022a; Nieuwenhuijsen et al, 2020; Nigatu et al, 2016; Salomonsson et al, 2018). Other interventions, more related to the specific field of expertise of occupational therapists such as: work on the occupational schedule, gradual reactivation in activities at home, support in maintaining life habits ( n = 1) are occupational therapy interventions that have been reported to have a positive impact on RTW (Marois et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimizing collaboration between the various RTW stakeholders is part of work-directed interventions, along with identifying barriers to return to work (Corbière et al, 2021; Jetha et al, 2021; MacEachen et al, 2020). For the job demands dimension, occupational therapists have also identified clinical interventions such as teaching strategies for managing relationships and emotions that can be associated with principles of cognitive-behavioral therapy (CBT), an approach on which are based most clinical interventions carried out in a RTW support context for people with CMDs (Corbière et al, 2022a; Nieuwenhuijsen et al, 2020; Nigatu et al, 2016; Salomonsson et al, 2018). Other interventions, more related to the specific field of expertise of occupational therapists such as: work on the occupational schedule, gradual reactivation in activities at home, support in maintaining life habits ( n = 1) are occupational therapy interventions that have been reported to have a positive impact on RTW (Marois et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although most targeted interventions are provided in an individual format, some of the interventions used by occupational therapists include group approaches (RTW support group). The use of this type of modality is relevant, with some studies indicating promising results with regards to the use of group approaches in work rehabilitation to support RTW of persons with CMDs (Corbière et al, 2022a; Eklund and Erlandsson, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study showed a significant improvement in work productivity associated with a brief group CBT intervention that was tailored to work-related issues ( 167 ).…”
Section: Pharmacological and Psychological Treatments For Workplace-r...mentioning
confidence: 99%
“…Die Befunde dieser Studie zeigen wie auch schon vorherige Ergebnisse, dass desgleichen die berufliche Situation, die Branche bzw. die früheren Tätigkeiten der Befragten berücksichtigt werden sollten [4,6,8,12,19]. Der Befund, dass psychisch erkrankte EM-Rentner*innen im Vergleich zu körperlich erkrankten EM-Rentner*innen bereits vor der Erwerbsminderungsrente weniger Stunden pro Woche gearbeitet haben, legt nahe, dass sich die beruflichen Teilhabeeinschränkungen bereits langfristig entwickelt haben.…”
Section: Diskussionunclassified
“…Der Befund, dass psychisch erkrankte EM-Rentner*innen im Vergleich zu körperlich erkrankten EM-Rentner*innen bereits vor der Erwerbsminderungsrente weniger Stunden pro Woche gearbeitet haben, legt nahe, dass sich die beruflichen Teilhabeeinschränkungen bereits langfristig entwickelt haben. Es sind also schon während der Berufstätigkeit vernetzte therapeutische, rehabilitative und betriebliche Konzepte notwendig, um das Eintreten einer Teilhabeeinschränkung zu verhindern [4,19,22]. Dabei zeigen die vorliegenden Befunde, dass Maßnahmen fokussieren sollten auf eine Stärkung der berufsbezogenen Selbstwirksamkeit und auf den Aufbau von Bewältigungskompetenzen beispielsweise bezüglich geringer wahrgenommener Anerkennung, zu anstrengend erlebter zwischenmenschlicher Aspekte sowie bezüglich Stress und Überforderung.…”
Section: Diskussionunclassified